Exploring governance structures of high altitude rangeland in Bhutan using Ostrom's Design Principles. Issue 1 (March 2018) - Tenzing, Karma; Millar, Joanne; Black, Rosemary
High altitude rangeland and livelihood systems in Bhutan are undergoing changes in resource availability, population and user rights. This paper explores the existing governance structures of high altitude rangelands in Bhutan using Ostrom's design principles as a framework for analysis. Qualitative interviews and focus group discussions were used to capture perceptions of 151 herders, sedentary livestock farmers and government officials across three case study sites. The research showed that most high altitude rangelands in the three case study sites have clear boundaries using natural and manmade landmarks along with a list of eligible users (design principle 1). Herders and livestock farmers have developed customary norms and rules to enforce and engender collective choice agreements for governance of high altitude rangeland (design principle 3). Community guards, appointed on a rotational basis, guarded communal pastures against infringement (design principle 4). Herders and livestock farmers have developed a graduated penalty system (design principle 5) and they were generally able to resolve most conflicts locally, however some were resolved through district courts (design principle 6). However, rights to organise (design principle 7) and a nested enterprise approach (design principle 8) did not feature explicitly in local governance discourses and narratives. Incongruence between provision and appropriation activities under existing governance structures of high altitude rangeland in the case study sites may be attributed to the assignment of incomplete property rights (e.g. lack of management rights) in the bundle of rights. The research demonstrated assigning management rights in the bundle of rights and conformance to design principle 2 are inextricably linked, and vital for sustainable governance of high altitude rangeland. One way to institutionalise Ostrom's design principles into natural resource governance is formalising and codifying them in the form of a written group constitution and by-laws. The role of government policies, acts and laws that inform and constrain high altitude rangeland management are explored and changes suggested for improving the current governance system of high altitude rangeland in Bhutan.